Experimental Evaluation of Effect of Flange Dimensions on Shear Behavior of NSC and SCC Double Tee Beams - Ali H. Aziz; Mohammad Zohair Yousif; Laye K. Salman (Engineering and Technology Journal, 2012)
This study deals with, experimentally, the effect of flange dimensions on shear behavior of normal strength concrete (NSC) and self-compacting concrete (SCC) double Tee beams. Twelve beam specimens as well as a series of control specimens are tested. The beam specimens were divided into two groups (based on concrete type) and each group are divided into five subgroups (based on flange dimensions).The webs dimensions, beam depth, beam length, spacing between webs, longitudinal (tension) reinforcement and transverse reinforcement (stirrups) were kept constant in all beam specimens. Experimental results showed that the ultimate capacity increased about (6%- 12) and (9%-20) when the flange width (dimensions) increased from (320mm) to (450mm) for NSC and SCC respectively. Presence of large compression flange lead to increase the stiffness of tested beams due to contribution of additional concrete parts, and this leads to increase in carrying capacity.